Too Hot to Nest? In a Hot Summer the Tortoise Chersina angulata Can Switch From Nesting to Facultative Viviparity - Kuchling, Gerald; Hofmeyr, Margaretha D. (Frontiers in Ecology and Evolution, 2022)
In a captive colony of Chersina angulata in Cape Town, South Africa, we observed in 2015/16 retention of the last egg clutch inside the female until the hatching stage was reached, conforming to the generally accepted definition of viviparity. Retrospective climatic analysis indicates egg retention until the hatching stage co-occurred with unusually hot summer weather: the average air temperatures in December 2015 and January and February 2016 were higher than during the preceding five and the following five years when facultative vivparity could not be observed. Late December and January appears to be the critical period for females to either deposit their last clutch of the nesting season into a nest, or to retain the last clutch for embryonic development inside the female. Over the 28 December to 24 January period the minimum, average and maximum air temperatures in 2015-16 were about 3°C higher than in the five following years. This association of facultative viviparity with unusual summer heat suggests that hot ambient temperatures at the end of the nesting season may cue females to switch from oviposition to facultative viviparity. Compared to incubation in a nest this phenotypic plasticity of the reproductive mode - to retain during hot summers the season’s last clutch inside the female - may buffer the developing embryos from excessive heat exposure: females can thermo-regulate by moving among microhabitats whereas sun exposed shallow nests cannot escape high ground temperatures. This novel reproductive strategy has the potential to enhance the resilience of species to global warming.